The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/plants9050559
|View full text |Cite
|
Sign up to set email alerts
|

Weed Classification for Site-Specific Weed Management Using an Automated Stereo Computer-Vision Machine-Learning System in Rice Fields

Abstract: Site-specific weed management and selective application of herbicides as eco-friendly techniques are still challenging tasks to perform, especially for densely cultivated crops, such as rice. This study is aimed at developing a stereo vision system for distinguishing between rice plants and weeds and further discriminating two types of weeds in a rice field by using artificial neural networks (ANNs) and two metaheuristic algorithms. For this purpose, stereo videos were recorded across the rice field and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…It is predicted that the global population will reach nine billion by 2050, and therefore, agricultural production must double to meet the increasing demands [1]. However, agriculture is facing immense challenges from the growing threats of plant diseases, pests and weed infestation [2][3][4][5] . The weed infestations, pests and diseases reduce the yield and quality of food, fibre and biofuel value of crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is predicted that the global population will reach nine billion by 2050, and therefore, agricultural production must double to meet the increasing demands [1]. However, agriculture is facing immense challenges from the growing threats of plant diseases, pests and weed infestation [2][3][4][5] . The weed infestations, pests and diseases reduce the yield and quality of food, fibre and biofuel value of crops.…”
Section: Introductionmentioning
confidence: 99%
“…A low-cost tool for identification and mapping of weeds at early growth stages will contribute to more effective, sustainable weed management approaches. Along with preventing the loss of crop yield by up to 34%, early weed control is also useful in reducing the occurrence of diseases and pests in crops [2,7]. Many approaches have been developed for managing weeds, and they normally consider current environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies use different kinds of datasets, from satellite to multispectral images and generic field observation to extract information for smart agriculture applications. There are important studies for soil fertility prediction [20], soil moisture [21][22][23], clay prediction by portable multispectral cameras [24], prediction for the condition of indoor plants through partial least squares [25], disease detection [26][27][28], and weed detection [29,30]. These models use an array of machine learning algorithms, including artificial neural networks (ANN), SVM, RF, KNN, multiple linear regression (MLR), etc., for various crops to predict, including ANN, SVM, RF, KNN, and MLR, etc., for various crops to predict their yield.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, low cost smart tools for identification and mapping of weeds at early growth stages will contribute to more effective, sustainable weed management approaches. Existing studies [26,96,97] have shown some approaches to detect weeds using UAV images; however, they only could achieve less than 90% of accuracy, hence more accurate weed detection approaches are desirable. The authors in [4] presented a shielded band sprayer to spray herbicides in weed, avoiding to spray on crops, hence increase the food quality and reduce the use of plant protection products.…”
mentioning
confidence: 99%